2019
DOI: 10.1002/jctb.6149
|View full text |Cite
|
Sign up to set email alerts
|

Cold oxygen plasma induces changes on the surface of carbon materials enhancing methanogenesis and N2O reduction in anaerobic sludge incubations

Abstract: BACKGROUND Conductive materials, such as activated carbon (AC), graphene and biochar, have recently been applied for enhancing methane (CH4) production in anaerobic digesters. However, few efforts have been made to develop engineered conductive materials for these purposes. The aim of this work was to synthesize carbon materials from pecan nut shells and peach stones to apply them in anaerobic sludge incubations for enhancing the methanogenic activity, as well as the reduction of nitrous oxide (N2O). RESULT Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Certainly, it was shown that the lack of pili and other cellular structures involved in electron transfer in microbial consortia can be compensated by the presence of CM [ 7 , 8 ]. Nevertheless, additional studies have indicated that the input of CM on AD processes goes beyond the stimulation of DIET because electric conductivity is not the only relevant parameter [ 6 , 9 ]. In fact, several physical-chemical properties of NMs, such as particle size, functional group, and surface area, drive the interactions between these materials and anaerobic microorganisms, ultimately determining the performance of anaerobic bioreactors during the production of methane from wastewater and solid residues.…”
Section: Immobilized Nms For Energy Productionmentioning
confidence: 99%
“…Certainly, it was shown that the lack of pili and other cellular structures involved in electron transfer in microbial consortia can be compensated by the presence of CM [ 7 , 8 ]. Nevertheless, additional studies have indicated that the input of CM on AD processes goes beyond the stimulation of DIET because electric conductivity is not the only relevant parameter [ 6 , 9 ]. In fact, several physical-chemical properties of NMs, such as particle size, functional group, and surface area, drive the interactions between these materials and anaerobic microorganisms, ultimately determining the performance of anaerobic bioreactors during the production of methane from wastewater and solid residues.…”
Section: Immobilized Nms For Energy Productionmentioning
confidence: 99%
“…More recently, activated carbon derived from organic wastes has been shown to effectively enhance the reduction of N 2 O by denitrifying microorganisms, in addition to improving methane production in anaerobic consortia. 9 Additionally, the conductivity of activated carbon favors direct interspecies electron transfer (DIET). 10 Carbon nanofibers have also been reported to enhance the anaerobic biotransformation of nitroaromatic compounds; moreover, chemical surface modification played a relevant role, indicating that functional groups, which are able to accept and donate electrons, such as quinone groups, take part as redox mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon increases methane production due to the porosity of its particles, which serve as a proper niche to support microbial growth. More recently, activated carbon derived from organic wastes has been shown to effectively enhance the reduction of N 2 O by denitrifying microorganisms, in addition to improving methane production in anaerobic consortia . Additionally, the conductivity of activated carbon favors direct interspecies electron transfer (DIET) .…”
Section: Introductionmentioning
confidence: 99%
“…Signals corresponding to the presence of C=C, C-O, O-H and C-H bonds were likewise present in the reference materials (GO and CC); however, the lower intensity obtained for these samples indicate the prominent functionality of the synthesized OX samples. Enriched surface functionality of organic xerogels can lead to an increase in the interspecies electron transfer since these groups can serve as redox mediators37 .…”
mentioning
confidence: 99%